DO NATIONAL CORE CURRICULA AND EDUCATION STANDARDS GUARANTEE EDUCATION QUALITY? - Duoblienė, Lilija; Bulajeva, Tatjana (Acta Paedagogica Vilnensia, 2008)
The article discusses the factors influencing the change of National Curricula in Lithuania. Since 1994 when the first version of National Core Curriculum appeared, it undergone many changes. New improved versions of it were regularly developed in 1997, 2002–2003. The latest draft version of 2007 has been just approved in the middle of the year of 2008. In spite of the fact that the quality of the curricula implemented in Lithuanian schools, is being improved all the time, the quality of Lithuanian students’ achievements has the tendency to decrease (as it became obviuos from the results of recent international comparative studies of student achievements). The research question arises whether this problem is rooted in the National Core Curricula document itself or in an inability of teachers to properly implement it. In this article only a part of a big study (2008) findings is being presented. In the first part the chronological analysis of the changes in the structure of different versions of National Core Curricula is presented. There are some theoretical curricular issues (Power, 1982; Kelly, 1999; Postman, 1996; McLaren, 1997, 2007) at conflict as well as guiding curricular principles (Power, 1982) discussed. In the second part there are some data from the teacher survey (N = 628) concerning their attitudes towards the existing National Core Curricula analyzed. The conclusions provide evidence that the majority of teachers are not satisfied with the quality of the main curricular document which they have to use while organising the educational process at Lithuanian schools.